Borders and the politics of space in late medieval Italy: Milan, Venice and their territories in the fifteenth century - Zenobi, L (2018)
This work is about medieval borders, about the culture and interactions by which they were shaped (the Politics of Space), and about the political communities which they bounded (Milan, Venice and their Territories). Its analysis centres on the long fifteenth century and particularly on the making of a new frontier between the Duchy of Milan and the Republic of Venice. Following decades of war, this process paved the way for a revival of economic and cultural connections across the region, and for the establishment of a political geography which was to remain virtually unchanged throughout early modernity. In contrast to traditional treatments of pre-modern borders, this thesis takes an all-encompassing approach to the topic, charting how borders were conceptualised (Chapter 1), negotiated (Chapter 2), disputed (Chapter 3), delimited (Chapter 4), crossed (Chapter 5), recorded (Chapter 6) and mapped (Chapter 7). To accomplish this, a wide range of sources, drawn from twenty different libraries and archives, is employed: from theoretical treatises to pragmatic records, from written chronicles to cartographic visualisations, from notarial documents to official correspondence. As a whole, the thesis makes three contributions. First of all, it demonstrates that medieval borders were not always vague zones of contact and conflict, nor were they just porous and muddled lines. In late medieval Italy, borders were in fact precisely located, minutely monitored and widely understood. Secondly, it develops a new methodological framework for understanding pre-modern modalities of territorial control, of which borders were but the material markers and symbolic expressions. That framework is the politics of space: the ensemble of political exchanges and social activities which underpinned and sometimes thwarted the assertion of territoriality. The third and final contribution is to the debate surrounding the paradigm of the territorial state in Italy, which this work challenges by deconstructing its borders and revealing its true spatial fabric.